Peripheral bare-metal stent implantation for a very-late stenosis of an aortic-left main Cabrol graft: a case report. Issue 3 (26th February 2022) - Carrera, Arcangelo; Contorni, Francesco; Gambacciani, Andrea; Neri, Eugenio
Abstract: Background: The surgical ascending aorta repair according to the Cabrol procedure involves the interposition of a prosthetic conduit between the aortic prosthesis and the native coronary ostia. Previous cases of the Cabrol conduit stenosis have been described, most of which presented as acute coronary syndromes due to thrombotic occlusion of the graft. Case summary: We present a case of stable exertional angina due to very-late stenosis of the coronary prosthetic conduit, successfully treated with trans-femoral percutaneous angioplasty and off-label implantation of a balloon-expandable bare-metal stent designed for peripheral artery disease. The multimodality imaging approach gave an essential contribution both to the assessment of the lesion and to the procedural planning. Despite the concerns about long-term results, a peripheral bare-metal stent was preferred over a standard coronary drug-eluting stent due to the remarkable dimension of the Cabrol conduit. Three years after the procedure, the patient is free from angina, and coronary computed tomography showed no significative luminal loss of the stent. Conclusion: Elective angioplasty of a Cabrol graft requires a careful planning through a multimodality stenosis assessment. Conventional coronary stents can be not large enough to ensure adequate apposition to the wide prosthetic conduit and peripheral bare-metal stents may be taken into consideration, at the price of unknown long-term outcomes.